Biomarker Fraktur Stres: Apa dan Kapan Harus Diuji? - Feliciana, Anastasia; Daniel, Daniel; Halim, Grace Suriadi; Seputri, Merryana; Anggunadi, Angelica (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Stress fractures are a common overused injury in both the general population, as well as the specialized population of athletes and military members.1,2 The incidence of stress fracture injuries is 21.1% in the athlete population, with higher rates in female athletes (9-13%) than male athletes (6.5%).3,4 Studies show 40% of athletes have experienced a stress fracture at some point in their career.3 Stress fracture injuries also account for 10% of orthopedic injuries and up to 20% of cases seen in sports medicine clinics. As many as 80-95% of stress fracture injuries occur in the lower extremities, with the commonest sites being the tibia, tarsal, metatarsal, and pelvis.3